Alienation in Ethiopian cinema: “T’eza” (“Morning Dew”) and “Səlä ʾänəči” (“About you”) in focus - Kindie Abebaw; Anteneh Aweke; Sintayehu Genet (PLoS ONE, 2025)
The main objective of this study was to show and analyze the representation of alienation in selected Amharic films. The films selected for the analysis include T’eza (Morning Dew) (2008) by Haile Gerima and Səlä ʾänəči (About you) (2009) by Belay Getaneh. The study explores how the selected Amharic films depict characters facing estrangement and marginalization in Ethiopian society, focusing on their struggles with alienation and identity. It aims to uncover the psychological and social dynamics behind these experiences and provide insights into themes of identity, loss, and societal exclusion. Using psychoanalytic and Marxist theories, the study analyzed the psychological, cultural, political, and social dimensions of alienation portrayed in these films. This study is sought with an interpretative paradigm and qualitative approach, employing narrative and descriptive designs. The films serve as the primary source of data, supplemented by secondary data from journals, books, and internet sources to provide additional context and theoretical support. The study highlights varied experiences of alienation among main characters, aiming to deepen understanding of this theme in Ethiopian cinema and inform efforts to address alienation in Ethiopian society. The significance of the study lies in its contribution to understanding this theme within the Ethiopian context, specifically through the lens of Amharic films. In conclusion, the study’s findings and analysis can inform discussions and interventions aimed at addressing alienation and its consequences in Ethiopian society.